What do Italian medical students read? A call for a library of good books on physicians for physicians. Issue 1 (1st June 2003) - Piccoli, G B; Mezza, E; Soragna, G; Burdese, M; Bermond, F; Grassi, G; Jeantet, A; Segoloni, G P
Abstract : Humanities are increasingly taught in medical schools based on the premise that sensitive and educated human beings may become better physicians. There have been few reports of what is offered in Italian medical schools and we have not been able to identify any published survey of student opinions.